THE SECOND-GENERATION PLATELET CONCENTRATES IN THE TREATMENT OF CHRONIC OSTEOMYELITIS: ONE MODERN REGENERATIVE SURGERY - Crisci, Alessandro; Raffaele, D’Adamo; Crisci, Michela (International Journal of Research -GRANTHAALAYAH, 2020)
Background: Hypothesis is that the use of fibrin rich in leukocytes and platelets advanced (A-PRF) in ulcer osteomyelitis on diabetic foot, allows recovery from this serious disease. In this study, the goal was to standardize the use of PRF in patients with osteomyelitis, to use this second-generation platelet concentrate, as a facilitator of healing. Methods: Authors produced and used peripheral blood A-PRF (1300 g × 8 min) membranes in 7 patients (all diabetic) with osteomyelitis and skin lesions for at least 6 months. Membranes, together with the supernatant liquid derived from compression, were inserted into the skin lesion down to the bone after surgical debridement. Evolution of the lesions over time was analyzed. Results: All seven patients had a positive Probe-to-Bone test, MRI detected cortico-periosteal thickening and/or foci of cortico-cancellous osteolysis adjacent to the ulcer. Gram-positive bacteria were found in our patients in 52% of cases. Cocci Gram +, such as S. Aureus (15.6%), S. -haemolytic (12.1%), S. Viridans (7.1%), and Bacilli Gram- such as Pseudomonas (10.6%), Proteus (7.8%), Enterobacter (5.7%) are present. Candida Albicans is present in 2.8%. Blood count showed no major changes. To date, skin lesions have healed in 6 of the seven patients treated (one patient for more than five years) with no signs of infection or recurrence. Conclusions: Results obtained on our patients suggest that PRF membranes may be a therapeutic option in this difficult to treat pathology.